Evaluation Of Physical And Mechanical Properties Of Wild Cherry Wood Heat-Treated Using The Thermowood Process - Süleyman Korkut; Ayhan Aytin (Maderas: Ciencia y Tecnología, 2015)
The aim of this study is to determine the change of some physical properties (oven-dry density, weight loss, swelling and anti-swelling efficiency) and mechanical properties (compression strength parallel to grain, bending strength, modulus of elasticity in bending, janka-hardness (cross-section, radial, tangential), impact bending strength and tension strength perpendicular to grain) of wild cherry woods after heat treatment under different durations. Specimens are exposed to temperature levels of 212 °C for time spans of 1,5 and 2,5 h. Based on the findings in this study, the results showed that oven-dry density, swelling, compression strength parallel to grain, bending strength, modulus of elasticity in bending, janka-hardness (Cross-section, Radial, Tangential), impact bending strength and tension strength perpendicular to grain values decreased with increasing treatment time.